Caring for children: a model of healthcare service quality in Bangladesh - Andaleeb, Syed Saad (© 2008 The Author, Oxford University Press, 2016)
This article was published in the International Journal for Quality in Health Care [© The Author 2008. Published by Oxford University Press] and the definite version is available at : http://dx.doi.org/10.1093/intqhc/mzn024 The Journal's website is at: http://intqhc.oxfordjournals.org/content/20/5/339